Transformasi Pendidikan Sosial berbasis Internasional dalam Mendukung Pendidikan Berkelanjutan - Qomariyah, Nurul; Siti Azizah (IAIN Madura, 2025)
International-based social education has become a crucial strategy in addressing the challenges of globalization. This concept emphasizes openness, inclusivity, and sustainability in the education system to develop globally competitive students. MTsN 3 Pamekasan has implemented various innovative programs to support international-based social education, such as participation in international academic competitions, the development of the Learning Resource Space (Rusuh) program, and the integration of pesantren curriculum with a modern approach. This study aims to analyze how the transformation of international-based social education at MTsN 3 Pamekasan contributes to sustainable education. Using a case study approach, this research examines policies, implementation, and the impact of the educational model applied in this institution. The findings indicate that this approach enhances students' academic achievements, strengthens digital literacy, and fosters 21st-century character and skills. However, challenges such as limited infrastructure and teachers’ readiness remain obstacles to its implementation. Therefore, sustainable strategies are needed to optimize the potential of international-based social education in improving the quality of education in Indonesia.